A layered drug nanovehicle toward targeted cancer imaging and therapy. Issue 7 (26th January 2016) - Guan, Shanyue; Liang, Ruizheng; Li, Chunyang; Yan, Dan; Wei, Min; Evans, David G.; Duan, Xue
Abstract : A layered drug nanovehicle with superior anticancer performance was fabricated via the co-intercalation of doxorubicin (DOX) and folic acid (FA) into the gallery of layered double hydroxides (LDHs), which can be potentially applied in medical imaging/therapy. Abstract : A layered drug nanovehicle was fabricated via the co-intercalation of doxorubicin (DOX) and folic acid (FA) into the gallery of layered double hydroxides (LDHs). This supermolecular nanovehicle (denoted as DOX–FA/LDH) demonstrates excellent fluorescence imaging and targeted therapy toward cancer cells. The nanovehicle shows a uniform platelet morphology with an average diameter of ∼171 nm. The unique host–guest interactions lead to a high dispersion of DOX, and in vitro tests reveal a legible and strong fluorescence imaging for the DOX–FA/LDH sample. In addition, the DOX–FA/LDH material produces a high anticancer activity toward HepG2 cells but rather low cytotoxicity to the normal cells (L02 cells), as a result of the overexpression of FA towards cancer cells. This work provides a facile approach for the design and preparation of a drug nanovehicle with significantly enhanced biocompatibility, diagnosis and targeted therapy, which can be potentially applied in medical imaging and chemotherapy.